Advanced Oxidation Processes for the Removal of Antibiotics from Water. An Overview - Cuerda-Correa, Eduardo Manuel; Alexandre-Franco, María F.; Fernández-González, Carmen (Water (Basel), 2020)
In this work, the application of advanced oxidation processes (AOPs) for the removal of antibiotics from water has been reviewed. The present concern about water has been exposed, and the main problems derived from the presence of emerging pollutants have been analyzed. Photolysis processes, ozone-based AOPs including ozonation, O3/UV, O3/H2O2, and O3/H2O2/UV, hydrogen peroxide-based methods (i.e., H2O2/UV, Fenton, Fenton-like, hetero-Fenton, and photo-Fenton), heterogeneous photocatalysis (TiO2/UV and TiO2/H2O2/UV systems), and sonochemical and electrooxidative AOPs have been reviewed. The main challenges and prospects of AOPs, as well as some recommendations for the improvement of AOPs aimed at the removal of antibiotics from wastewaters, are pointed out.